Coastal Lives : Nature, Capital, and the Struggle for Artisanal Fisheries in Peru - Viatori, Maximilian; Bombiella, Hector (Book collections on Project MUSE., 2019)
"This book shines a light on how changes to Peru's fishing policies and fishery management affect the lives of impoverished artisanal fisherman"--Provided by publisher.